Immunomodulating Profile of Dental Mesenchymal Stromal Cells: A Comprehensive Overview - Alessia Paganelli; Alessia Paganelli; Oriana Trubiani; Francesca Diomede; Alessandra Pisciotta; Roberto Paganelli; Roberto Paganelli (Frontiers Media S.A., 2021)
Dental mesenchymal stromal cells (MSCs) are multipotent cells present in dental tissues, characterized by plastic adherence in culture and specific surface markers (CD105, CD73, CD90, STRO-1, CD106, and CD146), common to all other MSC subtypes. Dental pulp, periodontal ligament, apical papilla, human exfoliated deciduous teeth, alveolar bone, dental follicle, tooth germ, and gingiva are all different sources for isolation and expansion of MSCs. Dental MSCs have regenerative and immunomodulatory properties; they are scarcely immunogenic but actively modulate T cell reactivity. in vitro studies and animal models of autoimmune diseases have provided evidence for the suppressive effects of dental MSCs on peripheral blood mononuclear cell proliferation, clearance of apoptotic cells, and promotion of a shift in the Treg/Th17 cell ratio. Appropriately stimulated MSCs produce anti-inflammatory mediators, such as transforming growth factor-β (TGF-β), prostaglandin E2, and interleukin (IL)-10. A particular mechanism through which MSCs exert their immunomodulatory action is via the production of extracellular vesicles containing such anti-inflammatory mediators. Recent studies demonstrated MSC-mediated inhibitory effects both on monocytes and activated macrophages, promoting their polarization to an anti-inflammatory M2-phenotype. A growing number of trials focusing on MSCs to treat autoimmune and inflammatory conditions are ongoing, but very few use dental tissue as a cellular source. Recent results suggest that dental MSCs are a promising therapeutic tool for immune-mediated disorders. However, the exact mechanisms responsible for dental MSC-mediated immunosuppression remain to be clarified, and impairment of dental MSCs immunosuppressive function in inflammatory conditions and aging must be assessed before considering autologous MSCs or their secreted vesicles for therapeutic purposes.